On-off-keying communication system based on low power receiver - Zhou, Lei (Nanyang Technological University, 2022)
The prevalence of bioelectronics puts forward new requirements for power consumption and materials of electronic equipment. In this report, on-off Keying(OOK) communication system is built on the basis of low power receiver to realize transmission and receiving of binary signal. BladeRF Software Defined Radio (SDR) was selected as the transmitter and the low-power receiver was built on PCB board.